Pengaruh Pemahaman Wajib Pajak, Sanksi Perpajakan Dan Tarif Pajak Terhadap Kepatuhan Wajib Pajak UMKM Di Labuhanbatu - Siboro, Safri Marjuki; Hansyah, Praida (Jurnal Manajemen Akuntansi (JUMSI), 2024)
This study aims to determine the effect of taxpayer understanding, tax sanctions and tax rates on compliance of UMKM taxpayers in Labuhanbatu. The method used in this research is quantitative descriptive method. The population in this study were 150 individual taxpayers who own UMKM in Labuhanbatu Regency and have been registered at KPP Pratama Rantauprapat. Sampling of this study using purposive sampling technique. The sample in this study used the Slovin formula with the results of 60 respondents. Testing in this study uses validity and reliability tests. The data in the study were also analyzed using the classical assumption test which consists of normality test, multicollinearity test, and heteroscedasticity test. Furthermore, after the classical assumption test is fulfilled, it is continued with multiple linear regression tests and hypothesis testing consisting of the coefficient of determination (R2) test, F model feasibility test, and T test. The results of the study indicate that partially (t test) tax understanding has a positive and significant effect on UMKM taxpayer compliance in Labuhanbatu while tax penalties and tax rates have a negative and significant effect on UMKM taxpayer compliance in Labuhanbatu. The results of the F test in this study show a significant 0.000 <0.005 so it can be concluded that tax understanding, tax penalties and tax rates simultaneously affect UMKM taxpayer compliance in Labuhanbatu.